PENERAPAN PELATIHAN CorelDRAW SEBAGAI UPAYA PENINGKATAN KOMPETENSI SISWA SMK IBRAHIMY 1 SUKOREJO - Nur Aida; Nur Laili Mukarromah; Zaehol Fatah (Jurnal Ilmiah Multidisiplin Ilmu, 2025)
Developing students' design skills in the aspect of skills has become a necessity and is important, so it is necessary to conduct design training using CorelDraw for the students of SMK Ibrahimy 1 Sukorejo. However, the challenge faced by the students of SMK Ibrahimy 1 Sukorejo at this time is the low interest of students in using design technology. This is evident from some students who still struggle to create designs with CorelDraw. This activity includes training in graphic design, logo creation, covers, and book cover design using the CorelDRAW application. The objective of this activity is for students to better understand graphic design and to create impressive creative works.